Towards decolonial ways of thinking Antarctic Social Sciences and Humanities - Lorenzo, Cristian A.; Estenssoro Saavedra, Fernando; Siqueira Tybusch, Jerônimo; Cenci, Daniel; Seitz, Ana Emerica
Stephen J. Pyne in his book “The Ice. A Journey to Antarctica” points out that ice structures in Antarctica present different variations in their form, shapes and movements. Such variations also happen in the diversity of knowledge production on the White Continent. Despite Antarctic Humanities and Social Sciences having grown in publications records over the last years, it is worth having a look at the way it has been shaped. This paper explores the literature on Antarctic Social Sciences and Humanities published in English, Spanish and Portuguese. In doing so, we collected data from papers published in journals indexed in Scopus, Scielo and Latindex in the period 2013-2019. The results highlight the tendencies in knowledge production concerning Antarctica, focus on the main questions and major topics of interest, the funding institutions, the author affiliations of the most cited papers, the scientific collaborations networks, the types of knowledge circulation between countries and regions, and the perceptions about the future of Antarctica. This paper aims to promote discussions on decolonial and geopolitical approaches in the production of knowledge on the Antarctic Social Sciences and Humanities. Fil: Lorenzo, Cristian A. Universidad Nacional de Tierra del Fuego; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Estenssoro Saavedra, Fernando. Universidad de Santiago de Chile; Chile Fil: Siqueira Tybusch, Jerônimo. Universidade Federal de Santa Maria; Brasil Fil: Cenci, Daniel. Universidade Regional Do Noroeste Do Estado Do Rio Grande Do Sul.; Brasil Fil: Seitz, Ana Emerica. Universidad del Salvador. Facultad de Ciencias Sociales. Instituto de Investigación en Ciencias Sociales; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina SCAR 2020 Antarctic Science - Global Connections Hobart Australia Scientific Committee on Antarctic Research